2005
DOI: 10.1021/es048950y
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Characterization of Aerobic Granules in a Sequencing Batch Reactor Treating Soybean-Processing Wastewater

Abstract: Aerobic granules were cultivated in a sequencing batch reactor (SBR) fed with soybean-processing wastewater at 25+/-1 degrees C and pH 7.0+/-0.1. The granulation process was described via measuring the increase of sludge size. The formation of granules was found to be a four-phase process, that is, acclimating, shaping, developing, and maturated. A modified Logistic model could well fit with the granule growth by diameter and could be employed to estimate the maximum diameter, lag time, and specific diameter g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
114
2
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 272 publications
(121 citation statements)
references
References 33 publications
4
114
2
1
Order By: Relevance
“…A plexiglass UASB reactor (2.1 liters; 10 cm in inner diameter) and a gas-solids separator portion (2.6 liters) was used in this study. The seeding aerobic granular sludge was taken from a lab-scale sequencing batch reactor treating soybean-processing wastewater (21 , was used as the feed for the enrichment culture described in the present study. The influent pH value was adjusted to 7.0 by adding 3 M NaOH or 3 M HCl.…”
Section: Methodsmentioning
confidence: 99%
“…A plexiglass UASB reactor (2.1 liters; 10 cm in inner diameter) and a gas-solids separator portion (2.6 liters) was used in this study. The seeding aerobic granular sludge was taken from a lab-scale sequencing batch reactor treating soybean-processing wastewater (21 , was used as the feed for the enrichment culture described in the present study. The influent pH value was adjusted to 7.0 by adding 3 M NaOH or 3 M HCl.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, the mean porosity of granules was estimated as 0.16 and 0.53, respectively, for the combined model and the protein model. Previous studies showed that the porosity of microbial aggregates with a diameter ranging from 1.0 mm to 10.0 mm could reach up to 80-90% (1,9,24). For these studies, the porosity of the microbial aggregates was calculated based on the following equations: …”
Section: Resultsmentioning
confidence: 99%
“…The protein and humic substances in EPS were measured using the modified Lowry method [14]. Image analysis, granule size, and specific gravity of granular sludge were determined using the method described by Su et al [15].…”
Section: Sampling and Analytical Methodsmentioning
confidence: 99%
“…Su et al [15] reported that the settling velocity and specific gravity were 37 m/h and 1.017, respectively, for an aerobic granular sludge. For this study, the settling velocity and specific gravity were 241 ± 29 m/h and 1.171, respectively, in G-SBR.…”
Section: Physical Properties and Eps Composition Of The Flocculent Anmentioning
confidence: 99%